Efetividade deliberativsa: estudo comparado de conselhos municipais de assistência social (1997/2006. - Eleonora Schettini Martins Cunha (2009)
This thesis is the result of an investigation accomplished with the Social Assistance Municipal Council in Belo Horizonte, Goiânia, Porto Alegre, Recife, and Rio de Janeiro. Its goal was to verify the factors that determine the deliberative effectiveness effective capability ofinfluence, control and decide public politics of these councils, as to check the deliberative democratic theorys explanatory potential to the study of these institutions. It was made a synchronic comparison between the different councils and a diachronic one with the samecouncils, considering the years 1997 and 2006. Therefore, a literature review about the State and its changes was produced, what made possible to explain the institutional changes that surround the councils creation in the structure of the Brazilian State. It was also produced aliterature review that shows the deliberative democratic theory and the study results in which are analyzed institutions that emphasize the deliberation as a mean to reach decisions. In what specifically refers to the councils, a contextualization of its creation process was prepared, asa documental analysis of its laws and internal regiments, to check its institutional drawing characteristics. The main documental analysis work was related to the ordinary and extraordinary meetings records of the selected years, to best know the deliberative process, and, from it, define the councils effectiveness. As complementary techniques, informalobservations of the meetings and semi-structured interviews with the counselors and the executive offices technicians were carried out. From the deliberative democratic theory, it was defined, to the councils, endogens variables, related to its institutional drawing anddeliberative process, and exogens variables, related to the associative dynamic and the municipal government political project. These variables allowed searching into the deliberation capability of the segments that set the councils, as the predominant function in these spaces and its institutional capability of producing bounded decisions, also the influenceof contextual factors. The results show that the deliberative democratic theory offers good parameters to the councils analysis. However, it presents some limits that need to be confronted, especially those related to the representation, the inequality that antecedes and is present on the deliberative processes, the deliberation types that can occur in differentmoments and spaces of the political system, and how they can relate among themselves. The outcomes also show important variations among the councils, mostly presented by the variables related to the deliberative process. Moreover, show a convergence in its deliberativeeffectiveness through time, independent of the context changes, what can be explained by the social assistance politic specificity.